2019
DOI: 10.1039/c8fd00149a
|View full text |Cite
|
Sign up to set email alerts
|

Direct optical excitation of dark plasmons for hot electron generation

Abstract: We demonstrate the excitation of dark modes and creation of hot electrons using linearly polarized light and scalable, cost-effective plasmonic surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…3c ), demonstrating the control of the structural parameters in the synthesis process. The number, energy, and spectral width of the polaritonic modes depends sensitively on the interparticle distance, number of layers, AuNP shape, diameter, and lattice type 35 , 36 , 53 , 54 . In consequence, an accurate control of all these parameters enables the design of tailored optical materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3c ), demonstrating the control of the structural parameters in the synthesis process. The number, energy, and spectral width of the polaritonic modes depends sensitively on the interparticle distance, number of layers, AuNP shape, diameter, and lattice type 35 , 36 , 53 , 54 . In consequence, an accurate control of all these parameters enables the design of tailored optical materials.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmonic dipole strength, which is relevant for the periodic coupling, scales with particle size, yielding small AuNPs less attractive for periodic dipole field coupling. For example, to observe well-defined plasmon polaritons, the minimum AuNP diameter is~25 nm 36,53,54 .…”
mentioning
confidence: 99%
“…Beyond SERS, the narrow peak width of the dark mode is also ideal for refractive index sensing. Recently, we showed that such plasmons can be excellent channels for generating hot-electrons that can be used for photocatalytical applications 24 . All the discussions presented in this study, together with the already well developed methods for the materials synthesis, show how promising they are for plasmonic applications, being also very intriguing from the theoretical point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Alaeian et al 25 studied spherical and octahedral nanoparticles superlattices and showed that they behave as metamaterials with magnetic response. Our recent studies also provided some theoretical analysis on the self-assembly of NMNPs, but the focus was mostly on experimental measurements and potential applications of these materials 23,24 . Furthermore, there is a number of theoretical studies on arrays of metal-insulator-metal particles (MIMs) [26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…The various applications of plasmonics require a control over the excitation of plasmonic modes. Some plasmon modes are better for optical enhancement and others for producing hot carriers [6]. Based on their lifetime and dipole moment plasmonic modes are divided into bright and dark [7,8].…”
Section: Introductionmentioning
confidence: 99%